2005
DOI: 10.1172/jci24354
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension from targeted ablation of chromogranin A can be rescued by the human ortholog

Abstract: The secretory prohormone chromogranin A (CHGA) is overexpressed in essential hypertension, a complex trait with genetic predisposition, while its catecholamine release-inhibitory fragment catestatin is diminished, and low catestatin predicts augmented adrenergic pressor responses. These findings from studies on humans suggest a mechanism whereby diminished catestatin might increase the risk for hypertension. We generated Chga -/-and humanized mice through transgenic insertion of a human CHGA haplotype in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
350
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 292 publications
(381 citation statements)
references
References 63 publications
25
350
2
4
Order By: Relevance
“…Unlike results from CgA knockout mice reporting concomitant changes in CgB and SgII expression (14,15,38), the down-regulation of SgII expression in isolated PC12 cells did not alter the expression levels of CgA and CgB (Fig. 1).…”
Section: Sgii As Necessary Factor In the Formation Of Dcgs In Pc12 Cementioning
confidence: 60%
See 2 more Smart Citations
“…Unlike results from CgA knockout mice reporting concomitant changes in CgB and SgII expression (14,15,38), the down-regulation of SgII expression in isolated PC12 cells did not alter the expression levels of CgA and CgB (Fig. 1).…”
Section: Sgii As Necessary Factor In the Formation Of Dcgs In Pc12 Cementioning
confidence: 60%
“…Uptake, storage, and exocytotic release of catecholamines are impaired in CgA-deficient mice (14,38,59), perhaps because of the combined absence of catecholamine binding/concentration properties of CgA (60) and the lower catecholamine affinity of the remaining cargo proteins, including SgII (38). Although additional experiments are required to further characterize the relationships between SgII and catecholamine metabolism, its necessary role for DCG formation in sympathochromaffin cells described in this study creates a convincing mechanistic link for the previously observed association between quantitative genetic variation at the SCG2 locus and human hypertension (2).…”
Section: Sgii As Necessary Factor In the Formation Of Dcgs In Pc12 Cementioning
confidence: 99%
See 1 more Smart Citation
“…26,29 -35 Our search began with the major proteins in the core of catecholamine storage vesicles: the chromogranins, which play a crucial role in the formation of such vesicles and hence in determining autonomic function. 1,5,7,8,54 Genetic Association With ESRD This study describes the association between hypertensive ESRD and common polymorphisms at CHGA, a gene now known to play critical roles within the sympathoadrenal system. 1,5,7,8,54 Here individual SNP and haplotype frequencies differed significantly between black patients with ESRD and ethnically matched nondisease controls (Tables 3 through 5, Figures 1 through 3).…”
Section: Heredity and Esrdmentioning
confidence: 99%
“…1,5,7,8,11,12 Indeed, inhibition of the biosynthesis of CHGA results in depletion of storage vesicles in chromaffin cells. 5,7,8 Within catecholaminergic cells, CHGA is co-stored and co-released with epinephrine and norepinephrine. In addition to their intracellular functions, CHGA is a pro-hormone/pro-peptide containing multiple recognition sites for specific endopeptidases, allowing enzymatic cleavage into smaller biologically active peptides.…”
mentioning
confidence: 99%